Microsoft Excel 2019 BIBLE / Michael Alexander, Dick Kusleika ; previously by John Walkenbach. - Alexander, Michael, 1972-; Kusleika, Dick; Walkenbach, John (Indianapolis, IN : Wiley, 2018)
The complete guide to Excel 2019Whether you are just starting out or an Excel novice, the Excel 2019 Bible is your comprehensive, go-to guide for all your Excel 2019 needs. Whether you use Excel at work or at home, you will be guided through the powerful new features and capabilities to take full advantage of what the updated version offers. Learn to incorporate templates, implement formulas, create pivot tables, analyze data, and much more. This is the only resource you need to navigate this powerful tool for business, home management, technical work, and much more.
Includes index.
Keywords: Microsoft Excel (Computer file).; Business -- Computer programs; Handbooks and manuals